Market orientation and performance of small and medium enterprises in Ghana: The mediating role of innovation - Bylon Abeeku Bamfo; Jerry Jay Kraa (Cogent Business & Management, 2019)
The study assessed the impact of market orientation on performance of small and medium enterprises (SMEs); the mediating role of innovation. The study was conducted on a total of 500 SMEs out of which 391 responses were received representing 78.2% response rate. Purposive and convenience sampling techniques were adopted in selecting the SMEs and questionnaires used to collect data. Explanatory research design was used. The study used Structural Equation Model (SEM) for data analysis and explored various relationships as presented in the hypothesis. The findings indicated that, market orientation variable of customer orientation positively and significantly predict performance; while competitor orientation positively predicts performance; however, not significant. Inter-functional orientation inversely and non-significantly impacts on performance of SMEs in Ghana. Innovation partially mediates between customer orientation and performance. Innovation fully mediates between inter-functional orientations and performance whereas innovation has no mediation between competitor orientation and performance. Businesses, particularly SMEs are encouraged to adopt and embark on market orientation practices and implement innovative practices so as to maximise performance.
Keywords: 650; Market orientation; innovation; performance; small and medium enterprises; Ghana